Mobile IP: A Solution for Transparent, Seamless Mobile Computer Communications - Redi, J.; Bahl, Victor (1998)
There is hardly a more pervasive trend in the world today than communications. The momentum towards anytime, anywhere and any-type of communication is fueled by advances in radio frequency technology, near-exponential sales of laptop computers and personal digital assistants (PDAs), as well as new models of business that expect and rely on instantaneous information availability. The commonly romanced vision of a traveling executive being able to have uninterrupted, uninhibited access to his ofﬁce mail, ofﬁce databases, personal ﬁles, and video conferencing while moving between geographically separated customer locations, airports and hotels is a reality that will happen in the next few years.